HERBAL REMEDY FOR OSTEOSARCOMA - CHALLENGING EVOLUTION - Pichaiyan, Vignesh; Mariyappan, Sasikala; Saravanan, Renuka; Ramalingam, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Bone cancer is the extremely rare type, which accounts for about 0.2% of all cancer. They metastasize the cancer cells to the bone parts which have an especially crucial mechanism of action while treating. It is treated with the advanced drugs, have effluent side effects when compared to the medicinal plants and phytoconstituents. The review effectively deals that the mechanism of action of different medicinal plants include Phyllanthus urinaria, Aralia elata, Punica granatum, Anemone altaica, and Potentilla chinensis and the phytoconstituents include corosolic acid, shikonin, thymoquinone, aloperine, and withaferin A. This review provides the detailed information about the importance of medicinal herbs in the treatment of bone cancer, besides the mechanism of action of several phytoconstituents in different cell lines used. In future, it is more useful for evaluating the treatment of bone cancer with phytoconstituents.